2011
DOI: 10.1007/s12043-011-0038-y
|View full text |Cite
|
Sign up to set email alerts
|

In vivo applications of X-ray fluorescence in human subjects

Abstract: X-ray fluorescence has been used to measure several elements noninvasively within living human subjects. Some description is given of the constraints imposed by this rather unusual form of analysis together with a brief listing indicating the range of elements for which such analyses have been developed. Measurements of two elements are then presented in more detail. Lead is measured in bone and has become a well-established tool in continuing research into the long term effects of lead. Strontium is also meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…These complications can be sorted into at least three main points. The first is tissue inhomogeneity . Many elements comprise soft tissue, mainly carbon, hydrogen, nitrogen, and oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These complications can be sorted into at least three main points. The first is tissue inhomogeneity . Many elements comprise soft tissue, mainly carbon, hydrogen, nitrogen, and oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…The first is tissue inhomogeneity. [3] Many elements comprise soft tissue, mainly carbon, hydrogen, nitrogen, and oxygen. Inhomogeneity segues into the second complication of thickness contributing to scatter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CBLI (μg.years/dl) was approximated by the product of the BLL and exposure duration (in years). It has been shown that 5–10% of the CBLI finds its way into the tibia [Hu et al, ; Chettle, ].…”
Section: Methodsmentioning
confidence: 99%